Overview of the IHO–Nippon Foundation GEOMAC project and its evolution over 15 years - Sumiyoshi, Masanao; Matsumoto, Kazufumi; Manteigas, Leonel; Fieldhouse, Lucy (The International Hydrographic Review, 2025)
The IHO-Nippon Foundation Cooperation Project, through the IHO Capacity Building Programme, has been providing opportunities for Category “B” nautical cartographer training at the UKHO for 15 years. Since the start of the Japan Capacity Building Project (JCBP) in 2008, which sought to develop and promote human capacity building of technical personnel in nautical cartography, through the Cartography, Hydrography and Related Training (CHART) and Geospatial Marine Analysis and Cartography (GEOMAC) projects by the partnerships of the Organizations shown in Fig. 1, the number of alumni from these projects is now approaching 100 from over 50 countries. This paper reviews the 15-year evolution of these projects and their achievements in supporting IHO Member States, as well as the current training course content.